I Wish, I Wonder, and Everything I Like: Living Stories of Piano Teaching and Learning With Young Children (LEARNing Landscapes, 2018)
The purpose of my inquiry is to learn more about how young children learn to play the piano through examining my own teaching practice. By using autoethnography as a creative nonfictional form of storytelling, I illustrate my learning journey in search for joyful and meaningful ways of exploring music and piano playing with young beginner students. In writing stories about my learning experiences as a piano teacher, I discuss the importance, value, and need for piano teachers’ autoethnographies.
Keywords: autoethnography; preschool piano pedagogy; piano teaching and learning stories